ANALYSIS OF BANK PERFORMANCE WITH INFORMATION TECHNOLOGY PERSPECTIVE - Yustinus Wahyu Agung Prasetyo; Mohammad Achmad Amin Soetomo; Mulya R. Mashudi (Universitas Tidar, 2021)
XYZ Bank provides several digital banking services for various segments, including the D-Bank mobile banking application, XYZ Online Banking, D-Card Mobile for credit card management, D-Financial for SMEs, D-BisMart. for the supply chain, as well as XYZ Trade Connect and Cash Connect for various customer businesses. It is known that 1) IT risk on the D-Bank application is still high. This can be seen from the number of risk events for IT system failure in its application. 2) The handling of IT problems is still not optimal, this can be seen from customer complaints that often reappear in the D-Bank application, such as failed logins, failed transactions and slow performance. 3) Lack of handling of IT Security services. This can be seen from the number of cyber-attacks that have successfully entered the D-Bank application. The final result shows that there are several domains and principles that need to be considered by management in order to improve the performance of information technology